Micropropagation Of Common Fig (Ficus Carica L.) Cv. Violette De Solliès - Ling, Wan Ting (2020)
Common fig or scientifically known as Ficus carica is one of the earliest cultivated crops belonging to the family Moraceae. Fig is native to Western Asia and introduced throughout the Mediterranean basin countries together with the human migration. It is an important food crop known for its high economic, nutritional and pharmaceutical values. The fig plant is commonly cultivated via vegetative propagation such as cutting, grafting and air layering but the multiplication rate of these conventional methods is low due to poor rooting and the presence of same contamination issues as mother plants. Plant tissue culture is an efficient alternative in mass propagation plants from selected plant stocks yielding plants that are disease and virus free. The current study aims to establish a micropropagation protocol for the common fig (F. carica L.) cv. ‘Violette de Solliès’ to mass propagate true-to-type fig plantlets via apical bud culture. Young apical buds were surface sterilized using different concentrations and duration of disinfectants and cultured on MS medium supplemented with 4 mg/L BAP for the establishment of in vitro cultures. Induced shoots were subjected to different concentrations of cytokinins (BAP, TDZ, Kn and Zn) and activated charcoal for the initiation of multiple shoots and selected cytokinin was combined with auxin (IAA) to evaluate the combined effects on the shoot multiplication. Individual shoots were transferred to WPM supplemented with different concentrations of auxins (NAA, IAA and IBA) for root induction. Rooted explants were acclimatized using different soil substrates (Jiffy pellet, peat moss, perlite, vermiculite and bio-char soil) and garden soil mixture.